The Analysis Study of Surgical Intervention of Degenerative Lumbar Spinal Stenosis: A Comprehensive Systematic Review - Muliagus Rimbana Chekmat; Imam Hidayat (International Medical Journal Corp. Ltd, 2025)
Background: Degenerative lumbar spinal stenosis (DLS) is a progressive condition characterized by narrowing of the spinal canal, leading to nerve compression and significant morbidity. Surgical intervention is often required for patients with refractory symptoms. Various surgical techniques have been developed, including laminectomy, discectomy, interspinous spacers, minimally invasive lumbar decompression (MILD), endoscopic decompression, and pedicle screw-rod instrumentation with fusion. However, the optimal surgical approach remains a subject of debate. Methods: This systematic review was conducted according to PRISMA 2020 guidelines. A comprehensive search was performed in PubMed, Embase, Cochrane Library, Web of Science, and Scopus to identify studies published between 2015 and 2025 that evaluated surgical interventions for DLS. Eligible studies included randomized controlled trials (RCTs), cohort studies, or case-control studies assessing surgical outcomes, including pain relief, functional improvement, complication rates, and reoperation rates. Results: After screening and full-text review, eight studies met the inclusion criteria. The results suggest that minimally invasive and endoscopic techniques are associated with improved postoperative recovery, lower complication rates, and enhanced functional outcomes compared to traditional open procedures. Laminectomy remains a widely used standard approach, but fusion techniques offer additional stability in select cases. The studies demonstrated a low risk of bias overall, particularly among RCTs, while retrospective studies exhibited greater methodological limitations. Conclusion: Minimally invasive and endoscopic surgical approaches for DLS offer promising outcomes in terms of pain relief, functional improvement, and recovery time. However, patient-specific factors, surgeon expertise, and long-term follow-up remain critical in determining the optimal surgical technique. Further high-quality, multi-center RCTs are necessary to strengthen the evidence base and guide clinical decision-making.